What Do We Talk About When We Talk About Northern Europe: Regional Identities in Lithuania (Politeja, 2017)
What Do We Talk About When We Talk About Northern Europe: Regional Identities in LithuaniaThe article examines Lithuanian regional identities with the emphasis on Northern European dimension. The key questions are: To what extent Northern European regional identity has been constructed among the Lithuanian political establishment (president, government, political parties) and how does this ‘Northern European’ idea look among other regional identities? The study will discuss instruments for the analysis of regional identity and will then delve into the inspection of political narratives of the Lithuanian president, two governments and political parties’ programmes in 2012-2017. The content and discourse analysis of political narratives among leading political figures in Lithuania will constitute a matrix of politically imagined regional identities. The article argues that trilateral Baltic regional identity has dominated Lithuanian political narratives in recent years with broader Northern European identity seeping in the Lithuanian self-reflections and gradually distancing from Central and Eastern European regional trademark.